Evidence the U.S. autism epidemic initiated by acetaminophen (Tylenol) is aggravated by oral antibiotic amoxicillin/clavulanate (Augmentin) and now exponentially by herbicide glyphosate (Roundup). (February 2018) - Good, Peter
Summary: Because certain hereditary diseases show autistic behavior, and autism often runs in families, researchers seek genes underlying the pathophysiology of autism, thus core behaviors. Other researchers argue environmental factors are decisive, citing compelling evidence of an autism epidemic in the United States beginning about 1980. Recognition that environmental factors influence gene expression led to synthesis of these views – an 'epigenetic epidemic' provoked by pervasive environmental agents altering expression of vulnerable genes, inducing characteristic autistic biochemistries in many mothers and infants. Two toxins most implicated in the U.S. autism epidemic are analgesic/antipyretic acetaminophen (Tylenol) and oral antibiotic amoxicillin/clavulanate (Augmentin). Recently herbicide glyphosate (Roundup) was exponentially implicated. What do these toxins have in common? Acetaminophen depletes sulfate and glutathione required to detoxify it. Oral antibiotics kill and glyphosate inhibits intestinal bacteria that synthesize methionine (precursor of sulfate and glutathione, and required to methylate DNA), bacteria that synthesize tryptophan (sole precursor of neuroinhibitor serotonin), and bacteria that restrain ammonia-generating anaerobes. Sulfate plus glutathione normally sulfate fetal adrenal androgen dehydroepiandrosterone to DHEAS – major precursor of placental/postnatal estrogens. Glyphosate (and heavy metals) also inhibit aromatase that turns androgens to estrogens. Placental/postnatal estrogens dehydrate/mature brain myelin sheaths, mature corpus callosum and left hemisphere preferentially, dilate brain blood vessels, and elevate brain serotonin and oxytocin. Stress-induced weak androgens and estrogen depletion coherently explain white matter asymmetry and dysconnection in autism, extreme male brain, low brain blood flow, hyperexcitability, social anxiety, and insufficient maternal oxytocin at birth to limit fetal brain chloride/water and mature GABA.